Digital health and financial good-governance: a mixed methods study of patient revenue capture in Malawi - Paul Kawale; Liz Grant; Claudia Pagliari (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Digital Health Information Systems (HIS) have potential to improve the finances of healthcare organisations in lower income countries through better tracking of patients and procedures, more timely billing, greater professional accountability and more informed decisions. However, little is known about how HIS influence these processes in such settings or how contextual and social factors mediate their implementation and impacts. # Objectives This study investigated whether, and through what mechanisms, the implementation of a modular HIS influenced revenue capture from patient billing in a large referral hospital in Malawi, drawing on the perspectives of complex sociotechnical systems, health system strengthening and ICT for good-governance. # Methods Retrospective mixed-methods case study involving documentary analysis of management reports, interviews with informed respondents and descriptive analysis of revenue data over an 8-year period. Key implementation stages were mapped against changes in patient revenue and triangulated with interview data to obtain a rich picture of the project over time. # Results Trends in measured revenue were obfuscated by fluctuations in data recording procedures, government reimbursement for patient services, patient traffic (due to public health interventions) and inflationary instability. Interviewees reported that the system had improved hospital finances through introducing greater transparency and accountability, thus preventing illicit practices such as informal payments. However, triangulating qualitative and quantitative data revealed that introducing the HIS had little effect on revenue (or possibly the reverse) until independent Ward Clerks were introduced to operate the systems' billing and payment functions, thus reducing opportunities for entrenched practices to be replicated digitally. # Conclusions Although it was not possible to draw firm conclusions about the effect of the HIS on billing and finance, qualitative findings from our study, coupled with data triangulation, align with other research indicating that HIS can help to improve efficiency and accountability in healthcare organisations, but that technology alone is unlikely to suffice. Further research is needed to understand the role of HIS as enablers of financial good-governance in low income country settings, to more robustly evaluate their impacts on work practices, efficiency and sustainability, and to understand the complex contextual and socio-cultural influences mediating these effects.